The Development of Character Value-Laden Module on Carbon Compound Materials and its Implication on Students’ Perception - Septina Maulia Putri; Sulastri Sulastri; Saminan Saminan (Proceedings of AICS - Social Sciences, 2017)
The study aimed to produce learning module in studying of carbon chemistry for third grade of senior high school students which has value of character and to analyze their perception after use it. This study referred to RD method with Borg Gall’s model which is divided into ten steps; research and collecting of information; planning; product developing; preliminary test; revision of preliminary test; field trial; revision of field trials; field implementation test; improvement of final product; and dissemination and implementation. Data wereanalyzedby using grade of module properness, teachers’ responses and students’ responses to the module and their perception after use it. Initially, the preliminary test was done by three validators and showed the percentage of 86% with a category of “very proper”. Then, field trials were graded by teachers among MGMP of chemistry in Banda Aceh and gave positive responses with a percentage of 84% of “very proper”. After that, the final product was implemented to students in SMAN 10 Fajar Harapan Banda Aceh and indicated that it was “proper” with a percentage of 76%. Besides that, dissemination and implementation stages were conducted for students in SMAN 1, SMAN 5 and SMAN 6 of Banda Aceh and their perception to that module was 85%. Therefore, it can be concluded that developing of module contained value of character was proper to be used in learning of carbon chemistry.  Keywords: module, learning values, character, carbon chemistry, perception.